Early fire detection using enhanced optical flow analysis technique - Khondaker, Arnisha; Khandaker, Arman (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.